ANALYSIS OF PHYSIOLOGICAL ERGONOMICS FOR NIGHT SHIFT WORKERS CORRELATED WITH SLEEP QUALITY AND TIME TO RECOVERY - Sugiono, Sugiono; Yuenyongchaiwat, Kornanong; Azlia, Wifqi; Lukodono, Rio Prasetyo; Putro, Wisnu Wijayanto; Sari, Sylvie Indah Kartika; Indrayadi, Bambang (JEMIS (Journal of Engineering & Management in Industrial System), 2023)
The worker’s recovery time from physical and mental workload is a crucial factor for office and factory management and it will effect on the working performance and design working system. The aim of this paper is to investigate the impact of physiological conditions on sleep quality and time to recovery for night shift electric steam power plant workers. The research is started with study literatures on physiology ergonomics, sleep quality measurement, human metabolism, expenditure energy graph and physical/mental workload. The research worked with 50 samples (age between 30 to 45 years old) who have duty to control the electric steam power plant on dynamic computer screen in the night shift. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was used subjectively to measure the value of sleep quality on 19 self – rated questions that assessed various sleep quality – related factor over the previous month. To know the speed of Time to Recovery (TTR), every worker perform a treadmill load with constant speed of 5 Km/hour for 10 minutes. Heart rate changes before activity, during activity (treatment) and TTR are recorded and it be analysed the pattern of relationship conducting to PSQI score. According to the data analysis, the higher PSQI score the longer time consume by workers to recovery. Moreover, Pearson statistic test results found that there is a strong relationship between sleep quality (PSQI value) and TTR for workers with value of 0.853. In sort, improving the quality of sleep for night shift electric steam power plant workers can definitely improve work performance on a shorter rest time or healthier conditions of workers.